As políticas públicas e suas contribuições para o enfrentamento do trabalho infantil no estado do Pará - BARRIGA, Yanne Cristine Cruz (2018)
The present work analyzes the contributions of public policies to the fight against child labor in the State of Pará. The term child labor in this work is referenced in Brazilian laws such as Law 8.069/90, Constitution Art. 227, and in international legislation such as the International Labor Organization (ILO) Conventions No. 138 and No. 182, which establishes as child labor the activities of children and adolescents who deprive them of their potential and dignity, which are detrimental to their physical and mental development. Regarding the State of Pará, an analysis of the Social Public Policies aimed at coping with this practice is made, because despite the existing legislation, it still persists. Emphasis is placed on the Bolsa Família, MPT in the School and the PETI (Child Labor Eradication Program), which recently underwent a new redesign. Therefore, it is sought to verify if these changes are effectively reaching their final goal: the confrontation with the practice of child labor in the State. At the end of this work, there is a certain disregard on the part of the public power of Pará, since the statistics in relation to the topic addressed have grown significantly in recent years, even with Public Policies focused on the clash with this practice.